STUDY AND EVALUATION OF DEVELOPMENTSAND RESEARCH ON AUDIT COMMITTEE EFFECTIVENESS DURING 2011 TO 2020 - Purnomo, Anugerah Septian; Arsjah, Regina Jansen (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2024)
The current development of the audit committee is it enough to reduce public investor panic towards information that is not in line with the expectations of public investors or only as a complement to the company's organs required by the regulator or does it play an important role in a company. This research is included in the type of literature study. during the last ten years, namely from 2011-2020 on research related to the audit committee. The research design uses a library data collection approach, uses a certain format, is formal and previously designed. This study uses secondary data with data collection techniques from accredited journal portals in Indonesia, namely Sinta 1 – Sinta 6. Overall, there are still inconsistent results among previous studies regarding the effect of audit committee effectiveness on company performance. From the side of studies that show a positive effect of the effectiveness of the audit committee on company performance, it is shown that the size, independence, and financial or accounting expertise of audit committee members can affect the quality of financial reports, earnings management, audit delay, solvency and profitability of the company, opinion going concern audit, tax avoidance, negative entrenchment effect, and CSR disclosure.